Traffic Rules in Electronic Financial Transactions (EFT) Networks - Vedran Batoš; Vlatko Lipovac; Antun Sertić (Promet - Traffic&Transportation, 1970)
This paper presents the traffic rules in the EFT (ElectronicFinancial Transactions) networks, based on the implementationof the solution called Gold-Net developed and implementedby Euronet Worldwide Inc. Following the traffic rulesin EFT networks, out of its worldwide experience, Gold-Netevolved a comprehensive and expandable EFT network solutiondesigned to meet an institution's needs today and in the future.It is an ITM (Integrated Transaction Management) solution,modular and expandable, and consists of a comprehensiveEFT software modules with ATM and POS driving capabilities.The combination of ATM management and the onlineconnection form the intercept processing control module. Asthe marketplace grows, this solution ensures that an ente1prisemay position itself for future growth and expanded service offerings.